Research on the Adaptation and Performance Communication Platform for Chinese Maonan Folk Songs - Long, Rongyu; Rattachaiwong, Nataporn; Liu, Lingling (Journal of Dhamma for Life, 2024)
This article explores the rich musical heritage of Maonan folk songs, a remarkable aspect of China's minority music culture that encapsulates the historical and cultural essence of the Maonan people. Current surveys indicate that the transmission and development of Maonan folk songs face significant challenges, placing this cultural treasure at risk of extinction. This study addresses the necessity of expanding communication channels for Maonan folk songs, aiming to increase public interest and appreciation through innovative adaptations and modern performance techniques. By presenting original song creations, this paper proposes strategies for the contemporary creation and performance of Maonan folk songs, offering recommendations to support the flourishing of China's national music culture.